Control of Viral Latency by Episome Maintenance Proteins. Issue 2 (February 2020) - De Leo, Alessandra; Calderon, Abram; Lieberman, Paul M.
Abstract : The human DNA tumor viruses Epstein–Barr virus (EBV), Kaposi's sarcoma-associated herpesvirus (KSHV), and human papillomavirus (HPV) share the common property of persisting as multicopy episomes in the nuclei of rapidly dividing host cells. These episomes form the molecular basis for viral latency and are etiologically linked to virus-associated cancers. Episome maintenance requires epigenetic programming to ensure the proper control of viral gene expression, DNA replication, and genome copy number. For these viruses, episome maintenance requires a dedicated virus-encoded episome maintenance protein (EMP), namely LANA (KSHV), EBNA1 (EBV), and E2 (HPV). Here, we review common features of these viral EMPs and discuss recent advances in understanding how they contribute to the epigenetic control of viral episome maintenance during latency. Highlights: Viruses have evolved elaborate mechanisms to maintain their genomes as passengers in host cells The oncogenic human herpesviruses, EBV and KSHV, and the small DNA tumor virus, HPV, persist as multicopy episomes EBV, KSHV, and HPV have dedicated EMPs that bind their viral genomes and tether to cellular metaphase chromosomes EMPs contribute to the epigenetic programming of latent viral genomes